Pengaruh Kualitas Produk, Promosi terhadap Penjualan Usaha Mikro Saat Pandemi Covid-19 - Muhammad Yusril Sobirin (Economic Reviews Journal, 2023)
The economic situation in Indonesia is currently experiencing a decline and even dived due to Corona Virus (COVID-19). With this topic, the most important production sector is the impact concentrated on Micro, Small and Medium Enterprises. One thing that is thought about is product quality and sales promotion, while simultaneous product quality and promotion are positive and significant for MSMEs. Micro businesses must focus on the factors that exist in product quality and promotion in building a business in order to increase sales again. Keywords: Product Quality, Promotion, Micro Business, Covid-19 ‘